ANALISIS PENGARUH PERUBAHAN PENGGUNAAN LAHAN TERHADAP DEBIT LIMPASAN PADA DAERAH ALIRAN SUNGAI BONDOYUDO KABUPATEN LUMAJANG DENGAN METODE RASIONAL - Kurniawan, Akbar; Aminata, Fransedo (Geoid, 2020)
Floods is an overflowing of a large amount of water on rainy seasons. Bondoyudo watershed is one of the most flood-prone area in Lumajang district. This research use rational method for calculate the surface runoff in each research areas. The formula is : Q = 0,278 CIA. From this research, based on rational method, flooded areas are Rowokangkung sub-district, Jatiroto sub-district, and Kedungjajang sub-district. In 2002, Rowokangkung sub-district and Kedungjajang sub-district ad excess runoff discharge as 3,65 m3/s and 2,23 m3/s. In 2010, Rowokangkung, Kedungjajang, and Jatiroto sub-district had excess runoff discharge as 3,72 m3/s, 2,42 m3/s, and 0,35 m3/s. In 2018, Rowokangkung, Kedungjajang, and Jatiroto sub-district had excess runoff discharge as 3,74 m3/s, 2,54 m3/s, 0,39 m3/s. he value of the effect of land use change on runoff discharge is calculated based on multiple linear regression and generated from the calculation of the coefficient of determination. The value of determination coefficient for Rowokangkung Sub-district, Kedungjajang Sub-district, and Jatiroto Sub-district are 92.5%, 93.1%, and 92.4%.